An innovative framework for the study and structure of airport business models - Kalakou, S.; Macário, R. (Case Studies on Transport Policy, 2013)
This paper aimed to explore different types of airport business models. The business model structure of Osterwalder and Pigneur (2010) can capture both the operation and the environment in which a company exists and for this reason it was employed to study the operation of twenty airports. These airports were organized into five categories (primary hub, secondary hub, business, low cost and cargo) according to the traffic type they are known to serve and their business profile. After comparing the business models of the airports within each category, the common elements were identified and their key differentiation parameters were designated. It was found that there is a pattern for the primary and secondary hub airports but not for the business, low cost and cargo airports. The outcome of the paper was the proposal of a new framework for the exploration of airport business models which introduces the concept of airport regeneration and incorporates the factors that impede airport managers from developing the business models they want.